Penerapan Metode De Moivre Dalam Perhitungan Premi Asuransi Jiwa Seumur Hidup Dengan Tingkat Suku Bunga Stokastik - Anita, Ardian Febri; Rosita, Silvia; Arsita, Sari (Program Studi Aktuaria, Fakultas Sains Teknologi dan Pendidikan, Universitas Tamansiswa Padang, 2023)
This study discusses the calculation of the annual premium value for whole life insurance with a stochastic interest rate following the Vasicek model using the mortalita De Moivre law method. To calculate the annual premium, what is needed is the present value of insurance or actuarial present value (APV) of ( and the cash value of a life annuity () which is influenced by a stochastic interest rate of (), probability of live, and probability of dying. Based on the results of the calculations and discussions that have been explained, it can be concluded that the premium value obtained is is Rp. 4,636.363.3 << Rp. 9,807,692.3 per year. From the results of the premium value obtained using the De Moivre law method, the premium value each year increases in line with the age of a person, it is conclueded that the higher a person’s age, the premium to be paid is also increases.